ARTROPODOFAUNA ASOCIADA A GEASTRUM TRIPLEX JUNGH GASTEROMYCETES , BASIDIOMYCOTINA ) . V REGIÓN , CHILE - Escudero, Viviana; Sáiz, Francisco (Acta Entomológica Chilena, 2022)
The purpose of the present paper is to survey the insects -Geastrum triplex relationships during the fruiting period of fungus. The study was carried out in the Reserva Forestal Peñuelas, V Región, under mediterranean chínate, between 06-01-1996 and 08-17-1996. Members of 23 species, distributed in 11 taxa of arthropods, were collected from fructifications of Geastrum triplex'. 13 mycetoxenes, 6 mycetophilous and 4 mycetobionts. Eleven out of twenty three species were found only in fructifications. The most abundant taxa were Collembola and Coleóptera, as well as in the area of study. The main conclusions are: a) Peñuelas is a new record for Geastrum triplex in Chile, b) biological aspects of development of principal mycetobionts, Caenocara humeralis White (Anobiidae) and Metophalmoides castrii Dajoz (Lathridiidae), are described, c) Geastrum triplex is recorded for first time as host of C. humeralis and M. castrii, d) a positive correlation between dammage of the gleba and the number of insects is established.